THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK PRICES IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Karniswati Gea; Vargo Christian L. Tobing (SEAN Institute, 2022)
The share price is a price set by a certain company regarding the ownership of a company. Information about stock prices is sought after by external parties and is very important information to be able to monitor the company's performance over a certain period. This study aims to empirically examine the effect of return on assets, earnings per share on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The population of this study is all manufacturing companies that have been listed on the Indonesia Stock Exchange from 2017-2021. The sampling technique used in this study is a non-probability sampling method with purposive sampling technique. From this technique, there are 19 companies that are sampled in this study. The data collection technique was carried out by collecting data from information on the financial statements of manufacturing companies that have been listed on the IDX from 2017-2021, while the data analysis method used in this study was descriptive statistical methods, classical assumption tests, and multiple linear regression analysis. Hypothesis test. The results of the T test analysis prove that the Return on Assets (ROA) variable has a significance value of 0.000 which is greater than 0.05 which means that ROA affects stock prices and h1 is accepted, while the Earning Per Share (EPS) variable has a significance value of 0.000 as well which is more greater than 0.05 so it can be concluded that earnings per share also has an influence on stock prices. Simultaneously, Return on Assets (ROA) and Earning Per Share (EPS) simultaneously affect stock prices.